Intracranial Pure Germinoma With Optic Nerve Infiltration. Issue 1 (March 2020) - Cohen, Devon A.; Bhatti, M. Tariq; Giannini, Caterina; Eckel, Laurence J.; Garrity, James A.; Chen, John J.
Abstract : Abstract: A 19-year-old man presented with a 3-year history of episodic headaches, right hemiparesis, and progressive vision loss in both eyes. Initially, extensive laboratory testing was unrevealing. MRI later demonstrated progressive enlargement and enhancement of the left optic nerve poorly correlated with the timing of his clinical manifestations. There was no clinical or radiological response to treatment with corticosteroids, mycophenolate mofetil, or rituximab administered empirically for possible inflammatory processes. Later in the disease course, he developed diabetes insipidus (DI), worsening vision to light perception bilaterally, severe cognitive decline, and spastic quadriparesis. Cerebrospinal fluid (CSF) beta human chorionic gonadotropin (β-hCG) was elevated. Eventually, a left optic nerve biopsy was performed, which was consistent with an intracranial pure germinoma with infiltration of the optic nerve and disseminated leptomeningeal disease. Although rare, intracranial germ cell tumors can primarily involve the anterior visual pathways and should be considered in the setting of DI and elevated CSF β-hCG.